2014
DOI: 10.1145/2602204.2602208
|View full text |Cite
|
Sign up to set email alerts
|

Using peeringDB to understand the peering ecosystem

Abstract: In this study we mine one of the few sources of public data available about the interdomain peering ecosytem: PeeringDB [1], an online database where participating networks contribute information about their peering policies, traffic volumes and presence at various geographic locations. Although established to support the practical needs of operators, this data also provides a valuable source of information to researchers. Using BGP data to cross-validate three years of PeeringDB snapshots, we find that Peerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…A key insight of our approach is that we can extract facility information per routing update through the analysis of BGP communities. Moreover, it is feasible to collect detailed facility maps from various public sources using techniques described in [50,68], thanks to the increasing openness in the sharing of colocation data to support a more flexible peering setup process or even automate it altogether [7,63]. Indeed, today the large majority of peerings are multilateral peerings that do not involve formal contractual agreements [100].…”
Section: Challenges and Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…A key insight of our approach is that we can extract facility information per routing update through the analysis of BGP communities. Moreover, it is feasible to collect detailed facility maps from various public sources using techniques described in [50,68], thanks to the increasing openness in the sharing of colocation data to support a more flexible peering setup process or even automate it altogether [7,63]. Indeed, today the large majority of peerings are multilateral peerings that do not involve formal contractual agreements [100].…”
Section: Challenges and Conceptmentioning
confidence: 99%
“…Direct peering is enabled by third party peering infrastructures (also referred as carrier-neutral peering infrastructures), such as colocation facilities and Internet Exchange Points (IXPs). These infrastructures are increasingly deployed in cities around the globe [50], and their members are growing constantly [61,68] supporting hundreds of thousands of peerings [100].…”
Section: Introductionmentioning
confidence: 99%
“…Lodhi et al [26] recent work on data mining PeeringDB, one of the few public sources of information about peering that consists of an online tool where Internet members contribute by inserting information regarding its policies, traffic amount, and geographic location. In this study the authors found consistent correlations between PeeringDB data compared to measurements from BGP prefixes advertised in the Internet.…”
Section: Related Workmentioning
confidence: 99%
“…traceroute), and (iii) BGP tables available in route servers [1,5,15,16,25,26,34]. IXPs have become attractive research targets because they represent a microcosm of Internet diversity [7], serving a variety of members such as ISPs of different nature, content providers, as well as public and private organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Content providers typically adopt an open peering strategy to assess potential peering relationships [3,43,48]. Under the open peering strategy, content providers are willing to peer with any AS that requests a peering relationship.…”
Section: Content Providersmentioning
confidence: 99%